Peran Bank Indonesia dalam Menjaga Stabilitas Ekonomi, Keuangan dan Moneter Berdasarkan Prinsip Syariah - Ramadhan, Fajri; Piter Berkat Harapan Ndraha; Muhamad Irwansyah; Sinta Puspita Dewi; Cindy Ayu Afriyanti (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
Bank Indonesia has a significant role in maintaining economic, financial and monetary stability in Indonesia, especially in the context of sharia principles. Sharia principles are the main guidelines in carrying out the functions of the central bank in order to create an economic system that is in accordance with Islamic values. This research aims to examine the role of Bank Indonesia in maintaining economic, financial and monetary stability by complying with sharia principles. The research method used is descriptive analysis and secondary data analysis. The research results show that Bank Indonesia has been active in developing sharia policy instruments, such as the Bank Indonesia Sharia Certificate (SBIS) and other monetary instruments that comply with sharia principles. Apart from that, Bank Indonesia is also involved in supervision and regulation of sharia financial institutions to ensure that economic activities run in accordance with sharia principles. Thus, the role of Bank Indonesia in maintaining economic, financial and monetary stability based on sharia principles is very important. Bank Indonesia has a major responsibility in ensuring that Indonesia’s financial system remains stable and in accordance with sharia values, so that it can support inclusive and sustainable economic growth in accordance with sharia principles.